Tāthbīq Nāmūdhāj āt-Tā ‘āllum āl-Qā’īm ‘ālā āl-Māshārī’ bīī-Istīkhdām Wāsāīth Powtoon līī-Tāhsīn Māhārāt āl-kālām Lādāy āt-Tullāb - Nabila, Khansa; Inayah, Inayah; Husna, Muhammad Ahsanul; Habibi, Ahyat; Ismail, Ismail (Mantiqu Tayr: Journal of Arabic Language, 2025)
One of the reasons students at Al-Azhar 29-BSB Islamic-School don’t yet have basic Arabic-skills is the lack of a learning model that encourages Arabic speaking practice, whether independently, in-class, or socially with school friends. Also, the project offers significant opportunities for active and cooperative learning, specifically through speaking practice using video-based media, and this practice is optimally supported by Powtoon. This study aims to characterize Project-Based Learning and its implementation; characterization of Powtoon in speaking through Project; and the challenges of this practice. This study employed qualitative-approachwith an-explanatory design. Data collected through observation, interviews, and questionnaires. Data analysed by Spradley-model includes: domain, taxonomic, component, and cultural theme analysis. The results showed that the implementation of the Project with Powtoon generally had a students'-confidence, creativity, and Arabic skills. Never the less, there were challenges, such as the limited features of the free version of Powtoon, variations in students' mastery, time-management, and shyness. This study concludes that although the Powtoon-based Project has great potential, the right strategy is needed to overcome these challenges so that Arabic learning is more optimal. Project using Powtoon in kalam, with Gen-Zare rarely done, so the opportunity to develop it is large in the form of research.